Heat suit training maintains the increased haemoglobin mass after altitude training camp in elite cyclists - Urianstad, T.; Rønnestad, B. R.; Odden, I.; Hansen, J.; Mølmen, K. S.; Cardinale, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Altitude training may increase haemoglobin mass (Hbmass) and improve sea-level endurance performance in athletes [1]. As a result, training and residing at high altitudes (>2000 m above sea level) have gained popularity among endurance athletes preparing for competitions at low altitudes [2]. However, the Hbmass gained during altitude camps typically diminishes rapidly upon returning to sea level [3]. Intriguingly, prolonged heat training-induced increase in Hbmass has been shown to be maintained for three weeks by performing only three 50-minute heat suit training sessions per week in elite cyclists [4]. The present study aimed to explore whether a similar approach can maintain increased Hbmass after an altitude training camp in elite cyclists. METHODS: Eighteen elite male cyclists, with a maximal oxygen consumption of 76.0 (4.8) mL/min/kg, completed a three-week training camp, residing and training >1890 m above sea level. In the weeks following the altitude camp, cyclists were divided into two groups: one group exercised with a heat suit that limited heat loss for 50 minutes three times a week (n=9), while the other followed their usual training routine (n=9). Heat sessions are described in detail elsewhere [4]. The total Hbmass was measured before the altitude training camp, one day after the camp, and three weeks later, i.e., after heat/usual training. Inferential statements about differences in change scores between groups were based on analyses of covariance, with baseline values defined as covariate and the post values as dependent variable. RESULTS: The three-week altitude training camp led to an overall increase in total Hbmass of 4.1 (2.5)%. The heat suit training group maintained their Hbmass for three weeks after the altitude training camp (0.2 (1.8)%), while the group of usual training displayed a reduction (-3.3 (0.8)%) in the same time period, which corresponded to a significant difference in Hbmass changes between groups during these three weeks (p